Renal artery thrombosis secondary to sepsis-induced disseminated intravascular coagulation in acute pyelonephritis - Jayoung Lee; Hee Chul Nam; Boo Gyoung Kim; Hyun Gyung Kim; Hee Chan Jung; Ji Hee Kim; Geun Seok Yang; Youn Jeong Park; Ka Young Kim; Yu-Seon Yun; Young Ok Kim; Jihan Yu (The Korean Society of Nephrology, 2012)
There are some reports of renal vein thrombosis associated with acute pyelonephritis, but a case of renal artery thrombosis in acute pyelonephritis has not been reported yet. Here we report a case of renal artery thrombosis which developed in a patient with acute pyelonephritis complicated with sepsis-induced disseminated intravascular coagulation (DIC). A 65-year-old woman with diabetes was diagnosed with acute pyelonephritis complicated with sepsis. Escherichia coli was isolated from both blood and urine cultures. When treated with antibiotics, her condition gradually improved. She suddenly complained of severe right flank pain without fever in the recovery phase. A computed tomography scan revealed right renal artery thrombosis with concomitant renal infarction. Prophylactic anticoagulation therapy was not suggested because of sustained thrombocytopenia and increased risk of bleeding. Flank pain resolved with conservative treatment and perfusion of infarcted kidney improved at the time of discharge. To our knowledge, this is the first case of renal artery thrombosis related to acute pyelonephritis with sepsis-induced DIC.